Pengaruh Advertising Value, Emotional Appeal dan Credibility Dalam Mendorong Click Ad Dan Purchase Intention Pada Iklan Digital Produk Properti Rexvin - Adiyati, Ria Risti; Sugiat, Maria (Al-Makki Publisher, 2025)
Social media has become a popular channel in property marketing strategies. Rexvin, a housing developer in Batam, uses Facebook to reach potential customers. Although digital campaigns have successfully increased leads, results have not been consistent in generating ad clicks or purchase decisions. This study examines the Advertising Value Model by adding Emotional Appeal, Advertising Credibility, Ad Click, Product Evaluation, and Incentive to their impact on Purchase Intention. The research uses a quantitative approach with PLS-SEM method through SmartPLS 3.0. Data was collected through online questionnaires from 217 respondents using purposive sampling. Results show that informativeness, entertainment, emotional appeal, and credibility have positive significant effects on advertising attitude, while irritation has no significant effect. Advertising attitude significantly influences ad click and purchase intention. Informativeness also directly affects ad click, while entertainment shows no significant effect. Ad click has positive effect on product evaluation, and product evaluation significantly influences purchase intention. Incentives also have significant effect on purchase intention. The study recommends strengthening advertising credibility, presenting clear information, applying emotional appeals, and maintaining incentive programs to enhance digital property advertising effectiveness.